Cross-border Purchases of Health Services : A Case Study on Austria and Hungary - Obermaier, Andreas J. (2012)
This paper explores the structure of cross-border health purchasing between Austria and Hungary and determines the size of this phenomenon as well as the barriers to a further increase. Austrian patients may receive health care treatment in Hungary in three different ways. First, patients may receive benefits in the context of the European Community Regulations 1408/71 and 574/72 (Category I patients). Second, outside those regulatory structures, Austrian patients travel to Hungary to receive medical treatment, especially dental treatment, and then seek reimbursement from their Austrian insurance (Category II patients). Third, some patients receive medical treatment in Hungary outside both schemes (Category III patients). There are about 42,500 Category I patients per year; and 58,000 Category II patients world-wide per year. An unknown but supposedly greater number of patients travel to Hungary to receive mainly dental treatment and cosmetic surgery (Category III). Most health actors in both Austria and Hungary do not regard cross-border purchasing of health services as having cost-saving effects. They put forward major legal, institutional, political, and psychological barriers, which inhibit public and private Austrian providers, to facilitate trade in health care and which inhibit individual patients to realize cost savings through capitalizing on lower health care prices in Hungary. Therefore, for the time being, trade in health care and patient mobility between Austria and Hungary is a circumscribed phenomenon in terms of quantities, and it will most probably remain so in the near future.